If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -3x = 3 + c Solving -2 + -3x = 3 + c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -3x = 3 + 2 + c Combine like terms: -2 + 2 = 0 0 + -3x = 3 + 2 + c -3x = 3 + 2 + c Combine like terms: 3 + 2 = 5 -3x = 5 + c Divide each side by '-3'. x = -1.666666667 + -0.3333333333c Simplifying x = -1.666666667 + -0.3333333333c
| 6(2x-3)=3(3x-7) | | -5(t-3)+7=6t-9 | | 10+2(x-3)=18 | | (6x+4)10x= | | 60+60+[4x-80]=180 | | 7(x-2)+7x=5(x+4)-7 | | 7x+y=215 | | y-1=0.33(x+3) | | xlogM+2logM-3xLogN+4LogN=0 | | 28.3=-12w | | 3+6x=43-4x | | 0.12x+0.9(x-2)=0.01(2x-3) | | -28=-(r-4)+7(7+4r) | | 41/6=31/3 | | 3x+7-2=2x+6-1 | | 2+5x=65-2x | | 6n=13z | | 30+63+[2x+7]=180 | | k+32=70 | | -2x+6=-3x+10 | | 24-7=10 | | -6-5x=-(-5+6x)-5 | | 8+18c-6= | | 1.63q=9.7 | | 4.2-2y=16.8 | | 14y-8y=24 | | 3x-2y-z=-24 | | 2.5x+3=23 | | (2x+4)2=5x-6 | | -2(z+5)=-10 | | 2x+18=23+8+x | | 1.68+m=14.29 |